Practice and Experience in Advanced Research Computing 2021
DOI: 10.1145/3437359.3465592
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the behavior of OpenMP Implementations with various Applications on two different Fujitsu A64FX platforms

Abstract: The development of the A64FX processor by Fujitsu has been a massive innovation in vectorized processors and led to Fugaku: the current world's fastest supercomputer. We use a variety of tools to analyze the behavior and performance of several OpenMP applications with different compilers, and how these applications scale on the different A64FX processors on clusters at Stony Brook University and RIKEN.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They found that the LLVM compiler generally outperformed on Xeon processors, but the gcc compiler outperformed for a small number of threads. With regard to ARMv8 architecture, Michalowicz et al [16] analyzed the performance of OpenMP applications with different compilers on the A64FX platform. But their evaluation was based on practical applications rather than specific directives.…”
Section: Measurement Of Openmp Overheadmentioning
confidence: 99%
“…They found that the LLVM compiler generally outperformed on Xeon processors, but the gcc compiler outperformed for a small number of threads. With regard to ARMv8 architecture, Michalowicz et al [16] analyzed the performance of OpenMP applications with different compilers on the A64FX platform. But their evaluation was based on practical applications rather than specific directives.…”
Section: Measurement Of Openmp Overheadmentioning
confidence: 99%